Police Powers: Use And Misuse - Majid, Mimi Kamariah (Journal of Malaysian and Comparative Law, 1999)
In 1976, a report regarding the handling of complaints against the police noted as follows: The performance of policy duty involves the exercise of powers which closely affect the liberty and rights of the individual, and is carrying out their duties police officers are inevitably exposed to criticism and complaints. In every police force some complaints are found on examination to be justified, but there is little doubt that others are made with the object of discrediting the police.